Severe motor aphasia after reinfusion of cryopreserved autologous stem cells after myeloablative conditioning. Issue 10 (27th July 2016) - Hausmann, Andreas; Fischer, Norbert; Breitkopf, Stephan; Menne, Franziska; Jess, Kerstin; Schmidmayr, Stefan; Wendtner, Clemens M.; Hentrich, Marcus
Abstract : BACKGROUND: Autologous peripheral blood stem cells (PBSCs) are usually cryopreserved before high‐dose chemotherapy (HDCT) and autologous peripheral blood stem cell transplantation (PBSCT). The freezing process requires the addition of cryoprotectants such as dimethyl sulfoxide (DMSO), which is vital for cell viability in frozen aliquots. DMSO has a number of well‐described side effects. However, severe neurologic side effects assigned to DMSO are exceedingly rare. CASE REPORT: A 64‐year‐old female underwent HDCT followed by PBSCT as consolidation therapy in relapsed high‐grade (Grade 3B) Stage IIIA follicular lymphoma. PBSCs were mobilized using granulocyte–colony stimulating factor and plerixafor after the second cycle of R‐DHAP (rituximab, dexamethasone, high‐dose Ara‐C, cisplatin) salvage chemotherapy. A total of 7.18 × 10 6 /kg body weight CD34+ cells were cryopreserved using 10% DMSO. HDCT was administered some weeks later followed by reinfusion of two bags of PBSCs, each containing 98 mL with 1.6 × 10 6 /kg body weight CD34+ cells. Within a few minutes the patient developed a motor aphasia and became very agitated. Brain imaging did not reveal any pathologic finding. After being transferred to the intensive care unit the patient's condition steadily improved and the motor aphasia resolved completely within 6 hours after its onset. CONCLUSION: This is, to our knowledge, the first report to describe an episode of severe motor aphasia during PBSCT. Given the close timely correlation with PBSCT, this episode appears to be caused by dimethyl sulfoxide (DMSO) and might possibly have been prevented by use of lower concentrations of DMSO.